Haloarchaea swim slowly for optimal chemotactic efficiency in low nutrient environments - Katie L. Thornton (Nature Portfolio, 2020)
Brownian motion places the ultimate limit on microorganisms’ ability to navigate. Thornton et al. show that Haloarchaea have a strategy of slow swimming and infrequent reorientation that exploits the randomising nature of Brownian motion to achieve optimal chemotaxis at the thermodynamic limit.